Implementasi Peraturan Daerah Daerah Istimewa Yogyakarta Nomor 2 Tahun 2018 tentang Penyelenggaraan Perlindungan Anak oleh DP3AP2KB dalam Rangka Menjamin dan Melindungi Hak Anak di Provinsi Daerah Istimewa Yogyakarta - Javier Moses Everd Ayorbaba; Sunny Ummul Firdaus; Maria Madalina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to analyze and find out the implementation of public policy regarding the Implementation of Child Protection in the City of Yogyakarta as well as the optimization of the DP3AP2KB for the City of Yogyakarta regarding factors that are obstacles to the Implementation of Child Protection in the City of Yogyakarta. The type of research used is empirical juridical. The nature used in this writing is descriptive with a focused interview research approach. The type of data in this writing is primary data obtained from observations in the field and secondary data originating from supporting sources such as journals, articles, regulations and other literature. The data collection technique used was a field study by conducting interviews with DP3AP2KB Yogyakarta City and the data analysis technique used was qualitative analysis.The implementation carried out by the Yogyakarta City Government regarding the Implementation of Child Protection has been very good, as evidenced by the regulations created as guidelines for the technical implementation of child protection. DP3AP2KB Yogyakarta City needs to optimize the role of related institutions to provide intelligence to every family in the Yogyakarta City area as a form of preventing obstacles that occur.